Seamless and secure handover scheme in mobile WiMAX - Rashid, Hamzah Fareed (2015)
Handover performance plays an essential role in ensuring that an excellent result is realized for most of the real-time applications in WiMAX networks. Generally, the entire interruption found in the handover process exists in three categories: i) link layer handover delay, ii) IP network layer handover delay, iii) security sub-layer handover delay. According to research the large portion of the delay associated with the handover process originates from user authentication and network entry and re-entry. Some types of soft real-time applications which include media streaming, however, require the smallest interruption for effective service. Unfortunately the existing design of the handover scheme lacks the ability to provide a seamless and secure connection [8][9]. Therefore, making use of this conventional technique will be unsuitable [22]. This thesis introduces an efficient design that can provide a seamless and secure communication especially over the subsequent handover; we named it (Seamless & Secure Subsequent Handover) 3SHO for short. This approach considers the use of a pre-authentication method and prior backhaul inter-communication, to generate a minimum delay that is suitable for some types of soft real-time application. Results obtained from analytical comparison and simulation; indicate that 3SHO approach achieves 72% improvement when compared to the standard [8][9], and 38% improvement over the enhanced scheme in [40]. When it comes to packet loss, the simulation results show that 3SHO approach achieves 76% improvement over the standard [8][9], and 56% improvement over the enhanced scheme in [40]. Parallel to the seamless handover, the proposed pre-authentication scheme proves to be a fine addition to our approach towards achieving a seamless handover with backward/forward secrecy characteristic. Furthermore,3SHO approach is verified using Automated Validation of Internet Security Protocols and Applications (AVISPA).